Prediction of Recurrent Atrial Tachyarrhythmia After Receiving Atrial Flutter Ablation in Patients With Prior Cardiac Surgery for Valvular Heart Disease - Chou, Ching-Yao; Chung, Fa-Po; Chang, Hung-Yu; Lin, Yenn-Jiang; Lo, Li-Wei; Hu, Yu-Feng; Chao, Tze-Fan; Liao, Jo-Nan; Tuan, Ta-Chuan; Lin, Chin-Yu; Chang, Ting-Yung; Liu, Chih-Min; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Surgical scars cause an intra-atrial conduction delay and anatomical obstacles that facilitate the perpetuation of atrial flutter (AFL). This study aimed to investigate the outcome and predictor of recurrent atrial tachyarrhythmia after catheter ablation in patients with prior cardiac surgery for valvular heart disease (VHD) who presented with AFL. Methods: Seventy-two patients with prior cardiac surgery for VHD who underwent AFL ablation were included. The patients were categorized into a typical AFL group (n = 45) and an atypical AFL group (n = 27). The endpoint was the recurrence of atrial tachyarrhythmia during follow-up. A multivariate analysis was performed to determine the predictor of recurrence. Results: No significant difference was found in the recurrence rate of atrial tachyarrhythmia between the 2 groups. Patients with concomitant atrial fibrillation (AF) had a higher recurrence of typical AFL compared to those without AF (13% vs. 0%, P=0.012). In subgroup analysis, typical AFL patients with concomitant AF had a higher incidence of recurrent atrial tachyarrhythmia than those without it (53% vs. 14%, P=0.006). Regarding patients without AF, the typical AFL group had a lower recurrence rate of atrial tachyarrhythmia than the atypical AFL group (14% vs. 40%, P=0.043). Multivariate analysis showed that chronic kidney disease (CKD) and left atrial diameter (LAD) were independent predictors of recurrence. Conclusions: In our study cohort, concomitant AF was associated with recurrence of atrial tachyarrhythmia. CKD and LAD independently predicted recurrence after AFL ablation in patients who have undergone cardiac surgery for VHD.